2020
DOI: 10.1016/j.sjbs.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant, antimicrobial and antiproliferative studies of four different extracts of Orthosiphon stamineus, Gynura procumbens and Ficus deltoidea

Abstract: BackgroundMedicinal plants are important source of drugs with pharmacological activities. Therefore, there is always rising demands to discover more therapeutic agents from various species. Orthosiphon stamineus, Gynura procumbens and Ficus deltoidea are high valued medicinal plants of Malaysia contain rich source of phenolic and flavonoid compounds. The aims of the present study were to evaluate anti-oxidant, antimicrobial and anti-proliferative effects on A549, HeGP2 and MCF7 cell lines of four different ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 37 publications
0
34
0
3
Order By: Relevance
“…Solvent extracts such as the polar solvent (ethanol) has a higher content compared to semi polar (chloroform) where an increase in TPC and TFC significantly increase antioxidant activity. This was supported by Kamran et al [9] where his recent study also indicated that semi polar solvent has higher antioxidant activity compared with polar solvent. Which was not surprising, as we know that flavonoids are a large group of phenolic secondary metabolites which are widespread among plants and are involved in many plant functions [49].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Solvent extracts such as the polar solvent (ethanol) has a higher content compared to semi polar (chloroform) where an increase in TPC and TFC significantly increase antioxidant activity. This was supported by Kamran et al [9] where his recent study also indicated that semi polar solvent has higher antioxidant activity compared with polar solvent. Which was not surprising, as we know that flavonoids are a large group of phenolic secondary metabolites which are widespread among plants and are involved in many plant functions [49].…”
Section: Discussionmentioning
confidence: 61%
“…It is a small plant up to 3 m tall, sometimes occurring as an epiphyte and exhibits low photosynthetic rates during its vegetative growth. Much research has been done to recognize the importance of this plant highlighting its antidiabetic [5,6], antinociceptive [7], antioxidant [8], antimicrobial [9] and anti-proliferative [10] uses. Historically, each part of this plant is known to provide benefits including reduced sugar levels in the blood [5], reduced blood pressure [10], contraction of the vagina after delivery [11], delayed menopause and also to reduce the risk of cancer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Statistically, it is estimated that there are 750,000 plant species on Earth, of which 1-10% are used as food and medicine by both humans and animals [1,2]. Medicinal plants display several pharmacological properties such as antioxidants [3], anti-diabetes [4], antibacterial [5], antiviral [6], anticancer [7], and anti-ulcer activities [8]. The medicinal value of these plants lies in a group of bioactive organic compounds (metabolites, secondary compounds) generally classified into alkaloids, saponins, flavonoids, tannins, glycosides, anthraquinones, steroids, and terpenoids and present at different quantities and qualities within the plants [9].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of different solvents on extraction yields, phytochemical constituents and biological activities such as antioxidant, antimicrobial and antiproliferative effects [36] or antidiabetic properties [12] of G. procumbens has been reported. For example, flavonoids such as myricetin, quercetin, kaempferol and apigenin were more highly detected in crude ethanolic extract than ethyl acetate or other fractions [22].…”
Section: Discussionmentioning
confidence: 99%